(3GdeSFhdjI GdLfGFjI ai eLGd GdeeGQSGJ GdEMJcGQjI (B: s (3OQGSI ebGQfI (B/ s - (3HOQ jYbhH jhSa Hf fLes; (3SejMI GdbdjhHis; (3TQja SjO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JfGhdJ QSGdI GdeSFhdjI GdLfGFjI ai eLGd GdeeGQSGJ GdEMJcGQjI Cf GdYGde Gdjhe jShOg fXGe EbJUGOi YGdei LOjO CaQRJg GdJWhQGJ h GdJZjQGJ GdLPQjI ai GdfXGe GdEbJUGOi GdYGdei(B: (3h dYd CHQR SeGJg JaYjd GdMQjI GdEbJUGOjI h ERdI GdYhGFb CeGe JOab GdeYdheGJ h GdJLGI GdSdYjI h GdNOejI h GdESJKeGQGJ GdNGQLjI h GdEJLGg UhH EbGeI JcJdGJ EbJUGOjI ai Xd Shb JfGaSjI YGdejI hGSYI JeJO Hjf cGaI CWQGa GdYGde(B: (3h Sjchf def jeJdc ebheGJ GdJbOe GdJbfi h GdQCSeGdi GdbOQI Ydi ONhd gPG GdfXGe h GdESJaGOI efg(B. (3h ai Xd EOQGc GdYGde cGaI h GdOhd GdfGejI NGUI ddJMOjGJ GdLOjOI GdJi CaQRgG gPG GdfXGe GdLOjO(B: (3cGf dG HO dgG ef EfJgGL ESJQGJjLjGJ LOjOI ddJfejI GdEbJUGOjI JJfGSH eY gPg GdJWhQGJ ef NdGd JWHjb JOGHjQ TGedI(B: (3dJbhjI hJYHFI GdehGQO GdEdfJGLjI h JYRjR caGAI ESJNOGegG h Pdc HEJHGY SjGSGJ EbJUGOjI JQJcR Ydi GdEUdGMGJ GdgjcdjI h JMQjQ h GYJeGO BdjGJ GdShb(B. (3h ai Xd gPG GdefGN SGO EJLGg fMh EUOGQ bhGfjf hWfjI dMeGjI GdefGaSI h ef GdeeGQSGJ GdEMJcGQjI GdJi ef TCfgG Cf JVQ HGdefGN GdJfGaSi GdPi jbhe Ydjg EbJUGO GdShb(B: (3h de jbJUQ gPG GdEJLGg Ydi hVY bhGfjf OGNdjI dMeGjI GdefGaSI h efY GdeeGQSGJ GdEMJcGQjI(B: (3Hd EeJO Edi hVY CWQ OhdjI h GbdjejI hKfGFjI dPGJ GdZQV Ydi GdUYjO GdOhdi Ch GdEbdjeis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2018s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B274-304s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3CfhGY h UhQ GdEMJcGQs; (3LQGFe GdeeGQSGJ GdEMJcGQjIs; (3MeGjI GdefGaSI h efY GdeeGQSGJ GdEMJcGQjIs; (3GdeeGQSGJ GdGMJcGQjI aj aQfSGs; (3MeGjI GdefGaSIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs